Hubungan Ketangguhan Mental dengan Kecemasan Bertanding pada Atlet Beladiri PPLP Jawa Tengah (Indonesian Journal for Physical Education and Sport, 2021)
This study aims to determine the relationship and level of mental toughness and level of anxiety competing in PPLP Central Java martial arts athletes. This study uses a quantitative method with a correlation design and sampling with a total sampling technique. Data collection via google form in the form of questionnaires and data analysis techniques with SPSS version 23.0. The results showed that there was no significant relationship between mental toughness and competing anxiety with the sig value. (2 tailed) .663 (p> 0.05) and the correlation coefficient value of -.0.48 which means that the closeness of the relationship is low and in the opposite direction. Furthermore, the responses to the questionnaires that were distributed were: 1). SMTQ: there are no mentally tough athletes 0 (0%), 2 athletes (2%) mentally less tough, 72 athletes (86%) mentally tough, and 10 athletes (12%) mentally very tough. 2). SCAT: 30 athletes (36%) had low anxiety, 46 athletes (55%) had average anxiety, and 8 athletes (9%) had high anxiety. The conclusion of this study is that there is no significant relationship between mental toughness and competing anxiety in the Central Java PPLP martial arts athletes and the level of mental toughness in the tough mental category and the level of competing anxiety in the average anxiety category. Suggestion: cooperation between athletes and coaches is needed to eliminate aspects that may interfere with athletes in training and competing in the hope of achieving the best performance and achievement.